Lavender Spa & Salon / Nurhawa Kassim ... [et al.] - Kassim, Nurhawa; Mayau, Ezra; Alan, Anilah; Sakar, Shazila; Rashid, Maylissa (2011)
"Going to a spa is a way of getting taken care of that is psychologically and culturally acceptable — and we can carry that feeling of being cared for with us for a period of time, and very often that can help us cope better with stress," says NYU professor of psychiatry Virginia Sadock, MD. Visiting a salon and spa is one of the best ways to unwind after a stressful day, as it allows you to pamper yourself and enjoy the relaxation of having a professional help you improve yourself. Whether you visit a spa for a massage and pedicure or if you want to go to a hair salon for a new hairstyle and colour, visiting a salon and spa can help you relax and enjoy life. Not only can the professionals at such an establishment help you improve your appearance and self-confidence, but they can also offer suggestions that can help you keep your muscles relaxed and hair looking beautiful in between visits. When deciding whether a spa and salon visit is a good option for you, it can help to know some of the benefits of going to one. In addition to helping you look your best at all times, a salon and spa can also help you feel your best by using relaxation techniques such as massage and aromatherapy to soothe you after a long and stressful day. Regardless of whether you have a stressful job or simply want to escape from the daily stresses of life for a couple of hours, making a visit to a salon and spa can help you accomplish just that. Depending on the spa you choose, you may have access to many different relaxation techniques, such as massages involving hot stones, body wraps, and saunas to help cleanse your body of toxins.